Spanish Higher Education: EMI Students’ Needs for Language Support Courses (ESP) - Krasauskyte-Sierra Ruiz, Rima; Chapman, Ana María (Vytautas Magnus University, 2025)
Given the endangered status of language support courses and the scarcity of research on the linguistic needs of EMI students in Spanish higher education, this study aims to investigate EMI students’ needs for language support and the potential of ESP courses in improving their English language skills. A mixed-method approach was used. The study results will contribute to filling the existing gap in EMI literature and inform stakeholders who are making major decisions on language support systems.
Keywords: Lengua inglesa técnica - Estudio y enseñanza superior; Investigación activa en educación; English medium instruction; English for specific purposes; English studies; Education